2012
DOI: 10.1007/s00125-012-2639-5
|View full text |Cite
|
Sign up to set email alerts
|

The ratio of visceral to subcutaneous fat, a metric of body fat distribution, is a unique correlate of cardiometabolic risk

Abstract: Aims/hypothesis The anatomic location of excess body fat has an impact on associated cardiometabolic morbidity, and visceral adipose tissue (VAT) is more pathogenic than subcutaneous adipose tissue (SAT). However, VAT or SAT alone provides little information regarding the relative distribution of body fat. We hypothesised that the propensity to store energy in VAT relative to SAT depots may be a correlate of cardiometabolic risk, and tested this hypothesis using the VAT/SAT ratio as a metric of fat distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
237
3
16

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 288 publications
(266 citation statements)
references
References 33 publications
(47 reference statements)
10
237
3
16
Order By: Relevance
“…Subcutaneous adipose tissue (SAT) has less facilitative or even protective effects on metabolic abnormalities compared to VAT. In fact, higher VAT/SAT ratio is associated with an increased cardio metabolic risk [29]. Taking these finding together, maintaining MHO phenotype was not associated with higher risk of incident Type 2 diabetes or CVD.…”
Section: Wwwscidocorg/ijdvrphpmentioning
confidence: 84%
“…Subcutaneous adipose tissue (SAT) has less facilitative or even protective effects on metabolic abnormalities compared to VAT. In fact, higher VAT/SAT ratio is associated with an increased cardio metabolic risk [29]. Taking these finding together, maintaining MHO phenotype was not associated with higher risk of incident Type 2 diabetes or CVD.…”
Section: Wwwscidocorg/ijdvrphpmentioning
confidence: 84%
“…Nonetheless, when the lipid storage capacity is exceeded, the store is diverted to other compartments outside the subcutaneous tissue, such as VAT, skeletal muscle and the liver, compromising their normal metabolic pathways and promoting unfavorable situations [34]. Some authors suggested that the SAT may have protective properties and that an absolute quantification of any deposit does not reflect its proportional distribution [8,35,36]. For example, a high volume of VAT or SAT may reflect both a high total abdominal fat mass and propensity to store For the regression, continuous variables (age, BMI, education in years of study, minutes of physical activity per week, food consumption score (simple carbohydrates, fat and processed meats, milk and dairy products, oils and fats, protective foods and alcohol) and dummy variables (SAH, DM, race, social class and smoking) entered the models visceral or subcutaneous fat.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a high volume of VAT or SAT may reflect both a high total abdominal fat mass and propensity to store For the regression, continuous variables (age, BMI, education in years of study, minutes of physical activity per week, food consumption score (simple carbohydrates, fat and processed meats, milk and dairy products, oils and fats, protective foods and alcohol) and dummy variables (SAH, DM, race, social class and smoking) entered the models visceral or subcutaneous fat. Thus, to separate the absolute amount of fat from a greater predisposition to store viscerally or subcutaneously, the use of the VAT/SAT ratio has been proposed as a relative metric of abdominal fat composition [36]. Hence, higher levels of subcutaneous fat in individuals with higher education levels may imply that these individuals would accumulate more subcutaneous fat than visceral fat.…”
Section: Discussionmentioning
confidence: 99%
“…Both types are important but attention has been directed to visceral adiposity owing to its association with various metabolic medical disorders 2 , cardiovascular disease and several malignancies. 3,4 Quantitative assessment of visceral obesity is important for evaluating the risk of these pathologies.…”
Section: Introductionmentioning
confidence: 99%